(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2020)
With steel structures help it is possible to construct buildings with individual dimensions and different functions, using typical design solutions. The increase in the load-bearing building structures unification level is facilitated by the use of the same transverse frames, which are installed with an equal step. It is possible to ensure the frame stiffness in its own plane by installing struts between the column and the beam. In this case, the crossbar must be calculated as a beam on the hinged supports on the frame columns and on the intermediate elastic supports with a given predetermined stiffness on the struts. By adjusting the struts stiffness and their installation scheme, it is possible to adjust and optimize the stress along the length of the crossbar